Gestão de resíduos sólidos urbanos em Angola: custos, benefícios e externalidades – estudo de caso na Província de Luanda (2010–2014) - Sousa Gonçalo, Agostinho (AfricArXiv, 2026)
Urban solid waste management (USWM) represents a major structural challenge in rapidly growing African cities, often characterized by landfill-based linear systems associated with high economic, environmental, and public health costs. In Angola, particularly in Luanda Province, there is a lack of empirical studies that integrate these dimensions. This study analyzes USWM between 2010 and 2014, combining direct public expenditures, the economic value of unrecovered recyclable materials, and associated health impacts. Based on official data, approximately 10.9 million tons of waste were landfilled, generating public expenditures exceeding 206 billion kwanzas and estimated economic losses of 162.9 billion kwanzas. Additionally, 4.8 million disease cases and 6,510 deaths were recorded, corresponding to estimated minimum health-related costs of 72.5 billion kwanzas. The findings reveal structural inefficiencies in the current system and highlight the need for integrated waste management policies focused on recycling, resource recovery, and improved coordination between environmental and public health sectors. Keywords: municipal solid waste; economic efficiency; recycling; public health; externalities; urban sustainability; Africa
Urban solid waste management in Angola: costs, benefits and externalities – a case study in Luanda Province (2010–2014)
This study provides an integrated analysis of economic, environmental, and health dimensions of urban solid waste management in Luanda, Angola.
Keywords: resíduos sólidos urbanos; eficiência económica; reciclagem; saúde pública; externalidades; sustentabilidade urbana; África